CRITICAL AND MATHEMATICAL THINKING IN THE STRUCTURE OF MATHEMATICAL COMPETENCE OF FUTURE MATHEMATICS TEACHERS - Chkana, Yaroslav; Martynenko, Olena (Physical and Mathematical Education, 2024)
Formulation of the problem. The impact of globalization on the complexity of social structures underscores the importance of developing critical thinking in the professional training of future mathematics teachers. A key component of their mathematical competence is mathematical thinking, which encompasses not only knowledge and skills but also the ability to analyze and solve complex problems. Despite the lack of a single definition, the contemporary scientific and pedagogical community acknowledges the existence and significance of mathematical thinking. Various approaches to defining mathematical thinking reveal its specific characteristics, particularly its association with abstract objects of study.Critical thinking, as an integral part of mathematical competence, facilitates purposeful intellectual activity, helping to delineate problems, analyze information, and find optimal solutions. Identifying and substantiating the complementarity of critical and mathematical thinking in solving mathematical problems is crucial for developing effective educational approaches in training future mathematics teachers.Materials and Methods. The study employs theoretical methods such as systematic analysis of research by domestic and foreign scholars, as well as systematization and generalization of practical experience.Results. The authors provide a characterization of critical and mathematical thinking within the cognitive activity structure during the formation of mathematical competence in future mathematics teachers. The main differences between these types of thinking are identified: abstraction and formalization in mathematical thinking, and systematic and contextual approaches in critical thinking. The study describes the specifics of various aspects of mathematical and critical thinking in solving mathematical problems and formulates a series of questions that further elucidate the unique characteristics of both types of thinking.Conclusions. Critical and mathematical thinking mutually support and enhance each other, with their complementarity creating a synergistic effect that ensures more comprehensive and effective problem-solving in mathematics. Considering these factors in the refinement of existing and the development of new educational technologies will promote the growth of mathematical competence among future mathematics teachers..
Keywords: mathematical competence; critical thinking; mathematical thinking; mathematical problems; future mathematics teachers